PENGEMBANGAN BUKU AJAR INOVATIF IPA TERPADU BERBASIS INKUIRI TERBIMBING SESUAI KURIKULUM 2013 DI SMP SE-KABUPATEN TAPANULI TENGAH - Bronika Septiani Sianturi; Jhonas Dongoran (Universitas Negeri Medan, 2019)
This study aims to produce a certain product or develop an existing product and test its effectiveness. Research and development procedure include stages: Potential and problems; Data collection; Product design; Design validation; Design revisions; Product I trial; Product I revision; Trial usage; Product Revision II; Mass product. The results of the analysis of teaching materials that have been developed on the subject matter of additives and addictive substances based on BSNP on aspects of content worthiness with a mean of 3.65, aspects of language worthiness with a mean of 3.70, aspects of the feasibility of serving with a mean of 3.60 are valid and do not need revision, the meaning is very decent. The results of the analysis of students' understanding of using material that has been developed obtained an average of 80.21. Meanwhile, the understanding of students who did not use teaching materials that have been developed obtained an average of 65.00. This shows that the understanding of students using teaching materials that are developed is higher than without using teaching materials that have been developed.Keywords: Research and Development (R & D, Guided Inquiry, Curriculum 2013.